Coupling hybrid of BN nanosheets and carbon nanotubes to enhance the mechanical and tribological properties of fabric composites. (August 2019) - Yuan, Junya; Zhang, Zhaozhu; Yang, Mingming; Wu, Liangfei; Li, Peilong; Guo, Fang; Men, Xuehu; Liu, Weimin
Abstract: Herein, composites of boron nitride nanosheets (BNNSs) and carboxylated carbon nanotubes (CNTs) with different compositions are prepared for the first time by covalent crosslinking using the carbodiimide reaction. The microstructure, functional groups, and phase composition of obtained BN1−x Cx (x = 0.25, 0.5 and 0.75) hybrid nanosheets are characterized by a variety of spectroscopic techniques and thermal analysis. Tensile and thermogravimetric testing results show that the fabric composites filled with BN1−x Cx hybrid nanosheets display remarkable enhancement in tensile strength and thermal stability, superior than that of pure fabric composites and composites reinforced by BNNSs and CNTs alone, thanks to the synergetic coupled effect between BN nanosheets and CNTs, as well as improved interface interaction between BN1−x Cx and resin matrix. Thereinto, the BN0.5 C0.5 with uniformly distributed CNTs and BN ultrathin nanosheets especially exhibits satisfactory performance. Furthermore, the BN0.5 C0.5 /fabric composites also manifest prominent anti-wear and friction-reduction characteristics attributed to the load-carrying capacity of CNTs and self-lubricating effect of BN nanosheets.